Comparison of the cardiometabolic profiles of adolescents conceived through ART with those of a non-ART cohort. Issue 8 (28th May 2022) - Wijs, L A; Doherty, D A; Keelan, J A; Burton, P; Yovich, J L; Beilin, L; Mori, T A; Huang, R C; Adams, L A; Olynyk, J K; Ayonrinde, O T; Penova-Veselinovic, B; et al.
Abstract: STUDY QUESTION: Is the cardiometabolic health of adolescents conceived through ART worse than that of their counterparts conceived without ART? SUMMARY ANSWER: The majority of cardiometabolic and vascular health parameters of adolescents conceived through ART are similar or more favourable, than those of their counterparts of similar age and conceived without ART. WHAT IS KNOWN ALREADY: It has been proposed that the cardiometabolic health of offspring conceived with ART may be unfavourable compared to that of their counterparts conceived without ART. The literature pertaining to cardiometabolic health of offspring conceived after ART is contradictory, but generally suggests unfavourable cardiometabolic health parameters, such as an increase in blood pressure (BP), vascular dysfunction and adiposity, as well as unfavourable glucose and lipid profiles. With over 8 million children and adults born through ART worldwide, it is important to investigate whether these early signs of adverse cardiometabolic differences persist into adolescence and beyond. STUDY DESIGN, SIZE, DURATION: The Growing Up Healthy Study (GUHS) is a prospective cohort study that recruited 303 adolescents and young adults conceived after ART (aged 13–21 years) and born between 1991 and 2001 in Western Australia. Their health parameters, including cardiometabolic factors, were assessed and compared with counterparts from the Raine Study Generation 2 (Gen2). The 2868 Gen2 participants were born 1989–1992 and are representative of the Western Australian adolescent population. At ∼17 years of age (2013–2017), 163 GUHS participants replicated assessments previously completed by Gen2 at a similar age. PARTICIPANTS/MATERIALS, SETTING, METHODS: Cardiometabolic parameters were compared between a total of 163 GUHS and 1457 Gen2 adolescents. Separate male (GUHS n = 81, Gen2 n = 735) and female (GUHS n = 82, Gen2 n = 722) analyses were conducted. Assessments consisted of a detailed questionnaire including health, lifestyle and demographic parameters, anthropometric assessments (height, weight, BMI, waist circumference and skinfold thickness), fasting serum biochemistry, arterial stiffness and BP (assessed using applanation tonometry). Abdominal ultrasonography was used to assess the presence and severity of hepatic steatosis, and thickness of abdominal fat compartments. Non-alcoholic fatty liver disease (NAFLD) was diagnosed if there was sonographic fatty liver in the absence of significant alcohol consumption. Chi 2, Fisher's exact and Mann–Whitney U tests, performed in SPSS V25, examined cohort differences and generalized estimating equations adjusted for the following covariates: singleton vs non-singleton pregnancy, birthweight (z-score), gestational age, BMI, smoking, alcohol consumption in the past 6 months and parent cardiovascular status. Arterial stiffness measures and waist circumference were additionally adjusted for height, and female analyses were additionally adjusted for use of oral contraceptives in the preceding 6 months. MAIN RESULTS AND THE ROLE OF CHANCE: In adjusted analyses, GUHS females had a lower BMI (22.1 vs 23.3 kg/m 2, P = 0.014), and thinner skinfolds (triceps, subscapular, mid-abdominal; 16.9 vs 18.7 mm, P = 0.021, 13.4 vs 15.0 mm, P = 0.027, 19.7 vs 23.2 mm, P < 0.001, respectively), whereas males were not significantly different. Waist circumference was lower in GUHS adolescents (males: 78.1 vs 81.3 cm, P = 0.008, females: 76.7 vs 83.3 cm, P = 0.007). There were no significant differences between the two groups in glucose, insulin, homeostatic model assessment for insulin resistance, low-density lipoprotein cholesterol, non-high-density lipoprotein cholesterol (non-HDL-C), total cholesterol (TC), alanine aminotransferase and high-sensitivity C-reactive protein in both sexes. In females, serum triglycerides were lower in GUHS adolescents (1.0 vs 1.2 mmol/l, P = 0.029). GUHS males had higher serum HDL-C (1.1 vs 1.0 mmol/l, P = 0.004) and a lower TC/HDL-C ratio (3.2 vs 3.6, P = 0.036). There were no significant differences in the prevalence of NAFLD or steatosis severity scores between the cohorts in males and females. GUHS females had less subcutaneous adipose tissue (9.4 vs 17.9 mm, P < 0.001), whereas GUHS males had greater visceral adipose thickness (44.7 vs 36.3 mm, P < 0.001). There was no significant difference in pre-peritoneal adipose thickness. Pulse wave velocity was lower in GUHS males (5.8 vs 6.3 m/s, P < 0.001) and heart rate corrected augmentation index was lower in GUHS females (−8.4 vs −2.7%, P = 0.048). There were no significant differences in BP or heart rate in males or females between the two groups. LIMITATIONS, REASONS FOR CAUTION: Despite the substantial study size and the unique study design of the ART cohort, we were unable to differentiate between different types of ART, due to the low number of ICSI cycles (e.g. IVF vs ICSI), draw definite conclusions, or relate the outcomes to the cause of infertility. Considering the differences in time points when both cohorts were studied, external factors could have changed, which could not be accounted for. Given the observational nature of this study, causation cannot be proven. WIDER IMPLICATIONS OF THE FINDINGS: Contrary to our hypothesis and previous findings focussing mainly on childhood, this study reports mostly similar or favourable cardiometabolic markers in adolescents conceived with ART compared to those conceived without ART. The greater visceral adipose thickness, particularly present in males, requires further investigation. While these findings are generally reassuring, future well-designed and appropriately powered studies are required to definitively address the issue of cardiometabolic health in ART adults. STUDY FUNDING/COMPETING INTEREST(S): This project was supported by NHMRC project grant number 1042269 and R.J.H. received education grant funding support from Ferring Pharmaceuticals. R.J.H. is the Medical Director of Fertility Specialists of Western Australia and a shareholder in Western IVF. He has received educational sponsorship from MSD, Merck-Serono and Ferring Pharmaceuticals. P.B. is the Scientific Director of Concept Fertility Centre, Subiaco, Western Australia. J.L.Y. is the Medical Director of PIVET Medical Centre, Perth, Western Australia. TRIAL REGISTRATION NUMBER: N/A.